Teknik Presenter Dalam Membaca Berita (Gaya Bahasa Program Mata Najwa) - Mochammad Sinung Restendy; Fatichatir Rizqiya; Mar’atul Mahmudah; Musmira Rizki Salam; Sri Umami (STAI Bumi Silampari, 2021)
The use of language style in journalistic language provides color and beauty in presenting information and news. This also affects how the information is received. So that the use of language styles in the media means disseminating various definitions of media messages and dominant ideological representations into the agenda of discussion. Mata Najwa Talkshow is one of the talk shows that uses language style in presenting the content of the program. From the linguistic aspect, the language used by Najwa Shihab in opening and closing events and in interviewing sources is very interesting. Najwa Shihab as a presenter always uses a choice of words (diction) and a language style that can attract the attention of viewers. With the use of diction and language style, Najwa Shihab can obtain information according to his wishes. The choice of the Mata Najwa program as the object of this research is because a newsanchor Najwa Shihab has his own language style in presenting his program. In addition, the language style used by Najwa played a role in emphasizing and beautifying the sentences he conveyed so that they became beautiful and interesting. This study analyzes the use of language styles in the Najwa Eye Program using a descriptive qualitative approach. Sources of data in the study are all sentences in the Mata Najwa Program which contain satire or satirical language styles. The technique used in this research is technical content analysis.